Mining Microbial Signals for Enhanced Biodiscovery of Secondary Metabolites - Reen, F.; Gutierrez-Barranquero, J.; O'Gara, Fergal (Humana Press, 2017)
The advent of metagenomics based biodiscovery has provided researchers with previously unforeseen access to the rich tapestry of natural bioactivity that exists in the biosphere. Unhindered by the "culturable bottleneck" that has severely limited the translation of the genetic potential that undoubtedly exists in nature, metagenomics nonetheless requires ongoing technological developments to maximize its efficacy and applicability to the discovery of new chemical entities.Here we describe methodologies for the detection and isolation of quorum sensing (QS) signal molecules from metagenomics libraries. QS signals have already shown considerable potential for the activation and "awakening" of biosynthetic gene clusters, bridging the existing divide between the natural product repertoire and the natural biosynthetic biodiversity hinted at by nature's blueprint. The QS pipeline from high-throughput robotics to functional screening and hit isolation is detailed, highlighting the multidisciplinary nature of progressive biodiscovery programs.